2014
DOI: 10.1002/ejsp.2012
|View full text |Cite
|
Sign up to set email alerts
|

Mortality salience and evaluations of in‐group versus out‐group critics: The role of criticism legitimacy and perceived threat

Abstract: Significant terror management research has examined the impact of mortality salience on evaluations toward in-group versus out-group and attitudinally similar versus dissimilar others. However, relatively little research has examined evaluations when group membership is disentangled from attitude similarity. The current research examined the impact of mortality salience on evaluations toward in-group and out-group critics when people are less likely to rely on group membership as a heuristic. In Experiment 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 69 publications
1
5
0
2
Order By: Relevance
“…Our study was the first to show that the mere suggestion of dating an out-group member was enough to threaten participants' self-esteem under conditions of MS, whereas the suggested in-group date reduced DEATH, DATING, AND DEFENSE 18 the need for worldview validation back to the control group level. Therewith, our study extends prior research relying on in-group critique as an interpersonal difference (Khoo et al, 2014;See & Petty, 2006). Noteworthy is that participants did prefer to date the in-group to the out-group member irrespective of condition.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our study was the first to show that the mere suggestion of dating an out-group member was enough to threaten participants' self-esteem under conditions of MS, whereas the suggested in-group date reduced DEATH, DATING, AND DEFENSE 18 the need for worldview validation back to the control group level. Therewith, our study extends prior research relying on in-group critique as an interpersonal difference (Khoo et al, 2014;See & Petty, 2006). Noteworthy is that participants did prefer to date the in-group to the out-group member irrespective of condition.…”
Section: Discussionsupporting
confidence: 76%
“…Participants did not change their evaluation of an in-group source depending on whether this source criticized or praised the university. Extending this line of research, Khoo, Hui, and See (2014) found that in-group participants stating a critique were evaluated more positively when the critique was justified than when it was unjustified.…”
Section: Between Intergroup and Interpersonal Differencesmentioning
confidence: 83%
See 1 more Smart Citation
“…Our findings extend past research in theoretically important ways. Whereas past research showed that threat affects people's attitudes toward ingroup critics (Ariyanto et al, 2010;Khoo & See, 2014), we extend it further by showing that threat also renders communications from ingroup members less persuasive and increases people's reluctance to share the critical communication with others in their social network, a key component of democratic engagement.…”
Section: How Threat Reduces Openness To Criticism By Changing Attribumentioning
confidence: 47%
“…Two recent experimental studies, however, suggest that the effect of threat may in fact be to reduce openness to ingroup critics. In one study, Khoo and See (2014) found that mortality salience led people to evaluate group critics who delivered unjustified criticism more negatively when they were ingroup members rather than outgroup members, with the opposite pattern for those in a dental pain condition. This research suggests that threat may reverse the preferential treatment of ingroup critics.…”
Section: The Influence Of Threat On Reactions To Criticismmentioning
confidence: 99%